Optimal Dark Tea Fertilization Enhances the Growth and Flower Quality of Tea Chrysanthemum by Improving the Soil Nutrient Availability in Simultaneous Precipitation and High-Temperature Regions - Jiayi Hou; Jiayuan Yin; Lei Liu; Lu Xu (Agronomy)
The simplex strategies of fertilizer management and problems caused by simultaneous precipitation and high-temperature (SPH) climate were the main factors that led to yield loss and quality decline in the continuous cropping of tea chrysanthemum (Dendranthema morifolium ‘Jinsi Huang’). In this study, with sustainable biofertilizers being proposed as a potential solution. However, their effects under such constraints are underexplored. In this study, we compared different proportions of a sustainable dark tea biofertilizer, made with two commonly used fertilizers, by their contributions to the morphological, photosynthetic, and flowering traits of D. morifolium ‘Jinsi Huang’. The results showed that increasing the dark tea biofertilizer application to 4.5 kg·m−2 significantly enhanced the soil alkali hydrolyzed nitrogen (596.53% increase), available phosphorus (64.11%), and rapidly available potassium (75.56%) compared to the levels in yellow soil. This nutrient enrichment in soil caused D. morifolium ‘Jinsi Huang’ to produce more leaves (272.84% increase) and flower buds (1041.67%), along with a strengthened photosynthetic capacity (higher Fv/Fm values and light saturation point). These improvements alleviated the photoinhibition caused by SPH climate conditions, ultimately leading to significantly higher contents of chlorogenic acid (38.23% increase) and total flavonoids (80.28%) in the harvested flowers compared to the control group. Thus, dark tea biofertilizer is a cost-effective and efficient additive for growing tea chrysanthemum in SPH regions due to improving soil quality and causing nutritional and functional components to accumulate in harvest flowers, which greatly promotes the commercial value of rural revitalization industries centered around tea chrysanthemum.